Competency in Nursing and Social Worker in Health Care Field: A Concept Analysis - Mana Abdullah Suwayyid Almansour , Bandar Hamad Shunayf , Najla Mesfer Abdullah Al Fayi , Hussain Yahia Al Beshr , Abdulaziz Hamad Ali Alrakah; Ibrahim Dafer Mohmmed Al yami , Rakan Hussain Mohammed Al Shariah , Mahdi Saleh Nemran Al Sharyah , Hussain Seraj Nasser Alsulum , Hamad Mohsen Saleh Al Saymah (Migration Letters, 2022)
INFORMAL CAREGIVERS primarily family members—are the foundation of rehabilitation, chronic care, and long-term support for older persons. The growing population of older persons and the changing health care delivery system (for example, shortened hospital stays) demand more of family caregivers and increase the toll on their health (Pinquart & Sorensen, 2007). To help them cope with these demands, nurses and social workers, who treat diverse older populations, must have cultural competence to enable them to practice effectively with caregivers (Pinquart & Sorensen, 2005).